Antiproliferative activity of Brassica nigra seeds extract in liver tissue of mice exposed to phenobarbital - Ibtehal Naseer Salman; Dalya Basil Hanna; Bahir Abdul-Razzaq Mshimesh (College of Pharmacy / Mustansiriyah University, 2022)
Hepatocellular proliferation is one of the most common causes of hepatocellular carcinoma (HCC), a type of cancer that is widely distributed disease. Hepatocellular carcinoma treatment has numerous barriers, including ineffectiveness, side effects, and drug resistance to currently available treatments. Previous studies showed that a high intake of Brassica vegetables has been associated to a decreased risk of a number of malignancies. The aim of this study is the evaluation of antiproliferative activity of Brassica nigra seeds extract in mice exposed to phenobarbital. Brassica nigra seeds where extracted; phytochemical analysis of the extract was done that including phytochemical screening tests and Gas chromatography-mass spectrometry (GC-MS) analysis. Antiproliferative activity of hydro alcoholic Brassica seeds extract has been studied by 800mg/kg and compare with control group (given normal saline), phenobarbital group (Phenobarbital 75mg/kg) and combination group (Brassica extract 800mg/kg+ Phenobarbital 75mg/kg). The GC-MS analysis revealed the presence of isothiocynate compound. Histologically phenobarbital induced severe hepatocellular proliferation (hyperplasia and hypertrophy), glass ground cytoplasm, while Brassica seeds extract produce improvement in histopathological changes that include mild scattered proliferation picture and eosinophilic cytoplasm. In comparison to phenobarbital group, Combination groups pretreated with Brassica nigra seeds for 14 days and phenobarbital for 7 days caused significant reduction relative liver weight and alanine aminotransferase (ALT) Brassica nigra seeds extract have isothiocynate as main compound it showed antiproliferative action on the liver tissue, implying that it may have a promising effect in minimizing the risk of liver cancer.